Studies on the production of beef from zebu cattle in East Africa. I. A description of the Muguga herd - Lampkin, G.H.; Lampkin, K. (Cambridge University Press, 1960)
Presents a brief description of the foundation stock at Muguga, Headquarters of the East African Veterinary Research Organisation. The breeding programme and type of management adopted at the centre are discussed.